The fibular incisura of the tibia with recurrent sprained ankle on magnetic resonance imaging - Mavi, Ayfer; Yildirim, Hanifi; Gunes, Hasan; Pestamalci, Turan; Gumusburan, Erdem (My University, 2002)
Objective: The aim of this study was to investigate the fibular incisura of the tibia in type I and II recurrent sprained ankle. Method: A total of 18 limbs (9 right, 9 left) were examined for the fibular incisura of the tibia by magnetic resonance imaging at Gunmar Magnetic Resosnace Imagaing Center between September 2000 to May 2001. This group consisted of 10 males and 8 females and their age ranged between 18-61 years. The control group was made up of 75 participating volunteers without previous history of trauma in the ankle. Results: The measurements of the length of the anterior and posterior facets, depth of the fibular incisura of the tibia and the distance between anterior margin of the tibia and anterior margin of the fibula in the patient group were visibly different from the measurements of the control group. In recurrent sprained ankle, the anterior and posterior tubercles were lengthier, the depth of the fibular incisura of the tibia was deeper and the fibula was more anterior than the control group. The measurements of the angle between anterior and posterior facets and the vertical distance of tibiofibular overlapping in the patient group were slight different from the measurements of the control groups. Conclusion: These characteristics, which were observed in the recurrent sprained ankles, may be anatomically predisposed to recurrent ankle sprains.
Keywords: Fibular incisura of the tibia; Incisural notch; Recurrent ankle sprains